ANALISIS PENERAPAN PEMBELAJARAN ANGKLUNG DI SEKOLAH DASAR - Syifa Mutmainnah Shafarina; Resa Respati; Aini Loita (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study analyses the implementation of angklung art learning in primary schools with a focus on implementation, learning methods, and factors that influence its implementation. Angklung as an Indonesian cultural heritage has high educational value in developing various aspects of students' abilities, ranging from cognitive, affective, to psychomotor. This study used descriptive qualitative method with data collection techniques through observation, in-depth interviews, and documentation conducted at one of the primary schools in Tasikmalaya Regency. The research subjects consisted of the principal, grade V teacher, and grade V students. The results showed that angklung learning has been implemented through four main methods: demonstration, group, hand sign, and imitation. However, the implementation is still not optimal due to the limited ability of teachers and the absence of a specialised music teacher. Supporting factors include the availability of complete infrastructure and teachers who have basic competence in angklung. While the inhibiting factors are the limited ability of teachers, lack of integration with the curriculum, and the lack of learning time allocation. This study concludes that angklung learning has great potential to be developed into a routine programme integrated into the curriculum with the support of continuous teacher training.